2014
DOI: 10.15517/rbt.v53i3-4.14598
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2,4-D, hydric stress and light on<i> indica</i> rice (<i>Oryza sativa</i>) somatic embryogenesis

Abstract: With the purpose of increasing the embryogenesis regeneration process in vitroplants obtained from somatic embryos of the indica rice variety CR-5272 (Oryza sativa L.), two independent experiments were performed. The first experiment consisted in the effect of combination of three concentrations of the gelling agent Phytagel (1.8, 2.4, and 3 gL-1) and four 2,4-D concentrations (2.26, 4.52, 6.78, and 9.05 M) on the induction and subsequent regeneration of embryogenic calli. On the second experiment, the pre-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 13 publications
3
20
0
2
Order By: Relevance
“…Gelrite was found to enhance callus induction and in vitro regeneration in Swarna (89.9%) and Mahsuri (93.4%) rice varieties [52]. Although use of agar as gelling agent to promote in vitro regeneration of rice has been reported [59][60][61]57], but Saharan et al [62] and Mensens et al [63] have reported higher regeneration frequency in indica rice varieties on media solidified with gelrite. Lin and Zhang [56] also have reported that 0.3% phytagel give higher callus induction.…”
Section: Resultsmentioning
confidence: 99%
“…Gelrite was found to enhance callus induction and in vitro regeneration in Swarna (89.9%) and Mahsuri (93.4%) rice varieties [52]. Although use of agar as gelling agent to promote in vitro regeneration of rice has been reported [59][60][61]57], but Saharan et al [62] and Mensens et al [63] have reported higher regeneration frequency in indica rice varieties on media solidified with gelrite. Lin and Zhang [56] also have reported that 0.3% phytagel give higher callus induction.…”
Section: Resultsmentioning
confidence: 99%
“…Varietas rekalsitran dikenal karena rendahnya kemampuan tanaman dalam produksi dan regenerasi kalus (Khatun et al, 2003). Kultur jaringan melalui embriogenesis somatik menggunakan eksplan kalus merupakan salah satu teknik yang sering digunakan dan merupakan langkah kunci dalam bioteknologi padi (Meneses et al, 2005). Embriogenesis somatik adalah proses perkembangan sel somatik membentuk sel embriogenik melalui tahap-tahap perubahan morfologi tanpa proses peleburan sel gamet (Quiroz-Figuera et al, 2006).…”
Section: Pendahuluanunclassified
“…Somatic embryogenesis, a regeneration technique effective in plant mass propagation, has been established in many species, e.g., Daucus carota (Lee et al, 2001;Nishiwaki et al, 2000), Oryza sativa L. (Meneses et al, 2005;Raval and Chattoo, 1993), Arabidopsis thaliana (Ikeda-Iwai et al, 2002;Luo and Koop, 1997), Phalaenopsis (Chen and Chang, 2006;Chung et al, 2006), and Cymbidium (Huan et al, 2004). The developmental process of somatic embryogenesis shares considerable similarity with that of zygotic embryogenesis (Zimmerman, 1993) because of the proposed conservation of molecular mechanisms underlying both processes (Higashi et al, 1998).…”
mentioning
confidence: 99%